The Holiness Composition in the Book of Exodus. - Tucker, Paavo N. (Mohr Siebeck, 2017)
Publisher's description: In this study, Paavo N. Tucker investigates different models of the formation of the Priestly literature in the Pentateuch by analyzing the relationship between the Priestly narratives in the Book of Exodus and the laws of the Holiness Code in Lev 17-26.
Keywords: Bible. -- Exodus -- Criticism, interpretation, etc.; Bible. -- Leviticus, XVII-XXVI.; Bible. -- Exodus; Bible. -- Leviticus, XVII-XXVI; Holiness.; Sainteté.; Holiness; Holiness Code -- Penteteuch -- Book of Exodus -- Priestly Literature -- Altes Testament -- Religionswissenschaft; Criticism, interpretation, etc.